The Correlation Between Self-Efficacy and English-Speaking Ability Among Vocational High School Students - Maura Zhaskia Widyareni; Rahayu Kuswardani (General English Education, 2026)
Speaking ability is essential in vocational education and may be influenced by psychological factors such as self-efficacy. This study investigated the correlation between self-efficacy and English-speaking ability among vocational high school students in Lumajang. A quantitative correlational design was employed with 70 Office Management students. Self-efficacy data were collected using an adapted questionnaire, and speaking ability was assessed using a speaking rubric. Instrument validity was reviewed by an expert, and reliability testing indicated acceptable internal consistency. Because one variable was not normally distributed, Spearman correlation was used as the main analysis. The findings revealed a very strong positive correlation between self-efficacy and speaking ability (Spearman ρ = .871, p < .05). Students with stronger beliefs in their speaking ability tended to perform better in speaking. These findings emphasize the importance of addressing psychological dimensions in English learning, particularly in vocational contexts where communicative competence is required for future professional settings.